Electrodeposition of copper from triethanolamine as a complexing agent in alkaline solution (2022)
ABSTRACT: The use of triethanolamine (TEA) as a cyanide-free electrolyte for copper electrodeposition was studied. The effect of TEA concentration on electrodeposition rate and cathodic adsorption during 3D copper growth was investigated. Linear sweep voltammetry (LSV), electrochemical quartz crystal microbalance (EQCM), scanning electron microscope (SEM), chronoamperometry and in situ surface-enhanced Raman scattering (SERS) were used to achieve a kinetic, thermodynamic, and mechanistic understanding. TEA forms stable complexes with copper, the most stable being Cu(TEA)(OH)3‾. Also, it acts as a surface modifier, promoting instantaneous nucleation and lower reduction rates to metallic copper. Thus, three-dimensional growth is controlled and, consequently, a smooth and homogeneous copper deposit is achieved.